Recombinant human interleukin 10 suppresses gliadin dependent T cell activation in ex vivo cultured coeliac intestinal mucosa - Salvati, V M (Copyright 2005 by Gut, 2005)
Background: Enteropathy in coeliac disease (CD) is sustained by a gliadin specific Th1 response. Interleukin (IL)-10 can downregulate Th1 immune responses. Aim: We investigated the ability of recombinant human (rh) IL-10 to suppress gliadin induced Th1 response. Patients and methods: IL-10 RNA transcripts were analysed by competitive reverse transcription-polymerase chain reaction in duodenal biopsies from untreated and treated CD patients, non-coeliac enteropathies (NCE), and controls. CD biopsies were cultured with a peptic-tryptic digest of gliadin with or without rhIL-10. The proportion of CD80+ and CD25+ cells in the lamina propria, epithelial expression of Fas, intraepithelial infiltration of CD3+ cells, as well as cytokine synthesis (interferon γ (IFN-γ) and IL-2) were measured. Short term T cell lines (TCLs) obtained from treated CD biopsies cultured with gliadin with or without rhIL-10 were analysed by ELISPOT for gliadin specific production of IFN-γ. Results: In untreated CD and NCE, IL-10 RNA transcripts were significantly upregulated. In ex vivo organ cultures, rhIL-10 downregulated gliadin induced cytokine synthesis, inhibited intraepithelial migration of CD3+ cells, and reduced the proportion of lamina propria CD25+ and CD80+ cells whereas it did not interfere with epithelial Fas expression. In short term TCLs, rhIL-10 abrogated the IFN-γ response to gliadin. Conclusions: rhIL-10 suppresses gliadin specific T cell activation. It may interfere with the antigen presenting capacity of lamina propria mononuclear cells as it reduces the expression of CD80. Interestingly, rhIL-10 also induces a long term hyporesponsiveness of gliadin specific mucosal T cells. These results offer new perspectives for therapeutic strategies in coeliac patients based on immune modulation by IL-10.